X-inactive specific transcript (XIST) can determine sex differences in cardiovascular drug responses: focus on RNA therapeutics - Yarovinsky, Timur O.; Ramgolam, Vinod S.; Knezevic, Iva R.; Stachenfeld, Nina S.; Bender, Jeffrey R. (Frontiers in Pharmacology, 2026)
Genetic, hormonal, anatomical, and environmental factors underlie sex differences in the prevalence and progression of cardiovascular disease and responses to therapeutics. The presence of two X chromosomes in the female genome decreases susceptibility to X-linked recessive disorders but imposes the need for random X chromosome inactivation as an epigenetic mechanism controlling gene dosage. Long non-coding RNA XIST is essential for transcriptional repression of genes on inactive X chromosome but may also act as a miRNA sponge for post-transcriptional regulation of gene expression and a scaffold for RNA binding proteins that provoke autoimmune responses. These features draw attention to XIST as an important drug development target by design or as an off target, including novel RNA therapeutics for genetic and cardiovascular diseases. Based on the extensive literature analysis, we postulate the hypothesis that XIST can determine sex differences in cardiovascular drug responses and propose several criteria for use in developing or evaluating responses to RNA therapeutics for cardiovascular disease in women. We hope that implementation of those criteria in the process of RNA therapeutics development may be helpful in reducing the risks of adverse effects in women.